The Perlindungan Notaris Terhadap Keterangan Yang Diberikan Pada Persidangan Tata Usaha Negara Yang Tidak Mengaplikasikan Hak Ingkar Dalam Persidangan - Sihite, Sri Rumada (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Notaries in carrying out their duties regarding deeds, agreements, and stipulations that must be required by statutory regulations and or desired are required to keep the deeds they have made confidential by the parties. Notary confidentiality that must be upheld can also be confidentiality, namely the confidentiality of professional ethics. Which states that the notary is obliged to keep secret all legal actions outlined in the contents of the deed and all information given to the Notary in the deed. The emergence of a lawsuit that was tried in the verdict 13/G/2018/PTUN-TPI, the author is interested in seeing how the notary's protection of the deed he made and how the legal remedies and legal consequences made by the panel of state administrative judges in the right of denial played by the notary in the state administrative trial. The research was conducted in a normative juridical manner. Using secondary literature data to research rules and norms. The conclusion obtained is that the protection of notaries against information given at the state administrative trial that does not apply the right of denial in the trial is certainly related to legal certainty for notaries whose rights are tried to file objections accompanied by reasons against a judge who tries the case. When referring to Article 52 of the Code of Criminal Procedure, which states the right of denial, the accused can submit a mitigating witness or commonly referred to as an Ade charge witness. An oath or promise intended for the notary profession which is carried out on the show of the laws and regulations themselves. The panel of State Administrative Judges held that the approval of the examination of Notary Anly Cenggana SH., through the object of the dispute a quo was contrary to the general principles of good governance, especially the principle of legal certainty and the principle of fair play.